2003
DOI: 10.1039/b211939k
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of optical and NMR spectral information with coordination variation for axially symmetric macrocyclic Eu(iii) and Yb(iii) complexes: axial donor polarisability determines ligand field and cation donor preference

Abstract: In Bleaney's theory of magnetic anisotropy, the second-order crystal field coefficient, B o 2 , is predicted to determine the dipolar NMR shift of paramagnetic lanthanide complexes in solution. This parameter has been measured directly, by analysing the europium emission spectra for a series of eight-and nine-coordinate axially symmetric complexes based on cyclen including aza-carboxylate ligands (e.g. DOTA), phosphonates (DOTP), phosphinates and several carboxamides (e.g. DOTAM). For both Yb and Eu complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
142
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 58 publications
12
142
0
Order By: Relevance
“…Although the precise location of the donor atoms in the coordination polyhedron cannot by determined from the emission spectra of europium(III) complexes, the 5 D 0 → 7 F 1 and 7 F 2 emission bands at 594 and 613 nm, respectively, may be sensitive to changes in coordination number. 18 The intensity of the ΔJ = 2 band is considered to be "hypersensitive" to the europium(III) coordination environment, whereas the ΔJ = 1 band consists of two transitions, the separation of which is determined by the axial crystal field coefficient. Although the relative intensities of these bands remained the same as water was added (not shown), the overall intensity of the spectra did diminish slightly due to nonradiative quenching of the europium-(III) excited state by water.…”
Section: Luminescence Studiesmentioning
confidence: 99%
“…Although the precise location of the donor atoms in the coordination polyhedron cannot by determined from the emission spectra of europium(III) complexes, the 5 D 0 → 7 F 1 and 7 F 2 emission bands at 594 and 613 nm, respectively, may be sensitive to changes in coordination number. 18 The intensity of the ΔJ = 2 band is considered to be "hypersensitive" to the europium(III) coordination environment, whereas the ΔJ = 1 band consists of two transitions, the separation of which is determined by the axial crystal field coefficient. Although the relative intensities of these bands remained the same as water was added (not shown), the overall intensity of the spectra did diminish slightly due to nonradiative quenching of the europium-(III) excited state by water.…”
Section: Luminescence Studiesmentioning
confidence: 99%
“…Curiously, the sign of this band, although negative in the spectrum of Yb1, is positive in the spectrum of YbDOTAMPh•H 2 O. The work of Dickins and coworkers 24 has shown that in the case of YbDOTAMPh both the magnitude and sign of this band are highly sensitive to the nature of the axial ligand of the complex. However, Yb1 and YbDOTAMPh•H 2 O both possess the same axial ligand, water.…”
Section: Near-infrared Circular Dichroism (Nir-cd) Spectroscopymentioning
confidence: 99%
“…Acquiring the CD spectrum of a chiral Yb 3+ complex in the near-infrared region intimately probes the coordination polyhedron of the ion and may allow important information to be gathered. Although this technique has been applied to the study of Yb 3+ complexes of other octadentate cyclen based ligands, 7,11,[24][25][26] the isolation of the two coordination isomers of the single ligand NO 2 BnDOTMA offers a unique opportunity to further probe the intimate nature of these two coordination geometries.…”
Section: Near-infrared Circular Dichroism (Nir-cd) Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations